Priming critical thinking: Simple interventions limit the influence of fake news about climate change on Facebook. (September 2019) - Lutzke, Lauren; Drummond, Caitlin; Slovic, Paul; Árvai, Joseph
Highlights: People rated fake and real Facebook news posts about climate change. We tested interventions that primed critical thinking to combat fake news. People trusted, liked, and shared fake news less after exposure to the interventions. The interventions did not negatively affect responses to real climate change news. Abstract: Fake news about climate change refers to fabricated information that mimics the appearance of legitimate reporting but is intended to mislead consumers. In light of concerns about fake news regarding climate change and other topics, researchers and media providers have been searching for ways to limit its spread and influence. This study tested the effect of two simple interventions, both of which primed critical thinking, on individuals' evaluation of the credibility of real and fake news about climate change on Facebook. Through an online experiment (n = 2, 750 participants), participants either read a series of guidelines for evaluating news online, or read and then rated the importance of each guideline; a control group was not exposed to guidelines of any type. We found that participants exposed to both types of guidelines reported a reduced likelihood to trust, like, and share fake news about climate change on Facebook. Importantly, exposure to these guidelines did not diminish individuals' likelihood to trust, like, or share legitimate climate news. The effect sizes for both types of intervention were small. However, because of the scale and speed at which social media operates, even a small reduction in users' likelihood to trust, like, and share fake news could be meaningful and impactful.